Does FLT3 mutation impact survival after hematopoietic stem cell transplantation for acute myeloid leukemia? A Center for International Blood and Marrow Transplant Research (CIBMTR) analysis. Issue 19 (17th June 2016) - Deol, Abhinav; Sengsayadeth, Salyka; Ahn, Kwang Woo; Wang, Hai‐Lin; Aljurf, Mahmoud; Antin, Joseph Harry; Battiwalla, Minoo; Bornhauser, Martin; Cahn, Jean‐Yves; Camitta, Bruce; Chen, Yi‐Bin; Cutler, Corey S.; et al.
Abstract : BACKGROUND: Patients with FMS like tyrosine kinase 3 (FLT3)‐mutated acute myeloid leukemia (AML) have a poor prognosis and are referred for early allogeneic hematopoietic stem cell transplantation (HCT). METHODS: Data from the Center for International Blood and Marrow Transplant Research (CIBMTR) were used to evaluate 511 adult patients with de novo AML who underwent HCT during 2008 through 2011 to determine whether FLT3 mutations had an impact on HCT outcomes. RESULTS: In total, 158 patients (31%) had FLT3 mutations. Univariate and multivariate analyses revealed an increased risk of relapse at 3 years in the FLT3 mutated group compared with the wild‐type (WT) group (38% [95% confidence interval (CI), 30%‐45%] vs 28% [95% CI, 24%‐33%]; P = .04; relative risk, 1.60 [95% CI, 1.15‐2.22]; P = .0048). However, FLT3 mutation status was not significantly associated with nonrelapse mortality, leukemia‐free survival, or overall survival. Although more patients in the FLT3 mutated group died from relapsed primary disease compared with those in the WT group (60% vs 46%), the 3‐year overall survival rate was comparable for the 2 groups (mutated group: 49%; 95% CI, 40%‐57%; WT group: 55%, 95% CI, 50%‐60%; P = .20). CONCLUSIONS: The current data indicate that FLT3 mutation status did not adversely impact overall survival after HCT, and about 50% of patients with this mutation who underwent HCT were long‐term survivors. Cancer 2016;122:3005‐3014 . © 2016 American Cancer Society . Abstract : FMS‐like tyrosine kinase 3 (FLT3) mutation status does not have an impact on overall survival after allogeneic hematopoietic stem cell transplantation. Pre‐emptive strategies to reduce relapse need to be investigated in patients who have FLT3 mutations to further improve outcomes after hematopoietic stem cell transplantation.